1996
DOI: 10.1111/j.1699-0463.1996.tb00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological significance of IgA1 proteases in bacterial colonization and pathogenesis: critical evaluation of experimental evidence

Abstract: IgA1 protease activity, which allows bacteria to cleave human IgA1 in the hinge region, represents a striking example of convergent evolution of a specific property in bacteria. Although it has been known since 1979 that IgA1 protease is produced by the three leading causes of bacterial meningitis in addition to important urogenital pathogens and some members of the oropharyngeal flora, the exact role of this enzyme in bacterial pathogenesis is still incompletely understood owing to lack of a satisfactory anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
211
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(218 citation statements)
references
References 128 publications
3
211
0
4
Order By: Relevance
“…SIgA forms a critical part of the intestinal immune system both in protection from harmful pathogens and in homeostasis [91]. It is especially suited to its role in the intestinal immune system as SIgA is highly protease resistant [92]. SIgA exerts its functions in defence against pathogens by neutralizing bacterial toxins, blocking adhesion molecules expressed by pathogens and transporting antigens and pathogens out of the LP back into the gut lumen [93] (Fig.…”
Section: Protective Responses Against Enteric Pathogensmentioning
confidence: 99%
“…SIgA forms a critical part of the intestinal immune system both in protection from harmful pathogens and in homeostasis [91]. It is especially suited to its role in the intestinal immune system as SIgA is highly protease resistant [92]. SIgA exerts its functions in defence against pathogens by neutralizing bacterial toxins, blocking adhesion molecules expressed by pathogens and transporting antigens and pathogens out of the LP back into the gut lumen [93] (Fig.…”
Section: Protective Responses Against Enteric Pathogensmentioning
confidence: 99%
“…[38][39][40] Also, a number of microorganisms express immunoglobulin-degrading proteases that have been implicated as virulence factors in aiding bacterial colonization. 8,41,42 Other examples of bacterial IgG-degrading proteases include Streptococcal SpeB that cleaves IgG in the upper hinge, 43,44 a Pseudomonas elastaselike enzyme, 45 Mirabilysin of Proteus mirabilis, 46 and Trepolisin of Treponema denticola.…”
Section: Proteolytic Cleavage Of Igg In the Hinge Regionmentioning
confidence: 99%
“…Thus, when it was observed that a number of these pathogens expressed IgA-degrading proteases (without similar actions on IgG), it was postulated to be a potential defense strategy against host immune surveillance in the GI tract. 42 The preferred sites of cleavage of secretory IgAs by various microbial proteases have been localized specifically to the hinge region. 76 These investigators generated a number of positional variants and deletion mutants to define certain alterations that could confer protease resistance.…”
Section: Igg Cleavage As a Potential Immune Evasion Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The two human IgA subclasses, IgA1 and IgA2, differ by an additional 13-aa sequence with O-linked glycosylation sites in the hinge region of IgA1 (4). The lack of 13 aa in the hinge confers on IgA2 its resistance to digestion by the bacterial proteases produced by microorganisms such as Streptococcus mutans, Neisseria meningitidis, and Haemophilus influenzae and may be the rationale for the predominance of IgA2 in mucosal secretions (5).…”
mentioning
confidence: 99%